2018
DOI: 10.1093/glycob/cwy016
|View full text |Cite
|
Sign up to set email alerts
|

Applications of a highly α2,6-selective pseudosialidase

Abstract: Within human biology, combinations of regioisomeric motifs of α2,6- or α2,3-sialic acids linked to galactose are frequently observed attached to glycoconjugates. These include glycoproteins and glycolipids, with each linkage carrying distinct biological information and function. Microbial linkage-specific sialidases have become important tools for studying the role of these sialosides in complex biological settings, as well as being used as biocatalysts for glycoengineering. However, currently, there is no α2,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…24 R -sialyltransferases -sialidases based on their reverse activity. 25,26 Furthermore, glycosyl transfer catalysed -N-G Treversible. 27 However, to the best of our knowledge there is no report on galactosyltransferases exhibiting reverse transfer from lactose.…”
mentioning
confidence: 99%
“…24 R -sialyltransferases -sialidases based on their reverse activity. 25,26 Furthermore, glycosyl transfer catalysed -N-G Treversible. 27 However, to the best of our knowledge there is no report on galactosyltransferases exhibiting reverse transfer from lactose.…”
mentioning
confidence: 99%
“…In this work, a one-pot four-enzyme reaction which took place in D 2 O as a reaction solvent was carried out to synthesize 9a and 9b . A comparable biosynthetic approach (but using H 2 O instead of D 2 O) was recently applied by Both et al for the synthesis of X-Gal-α-2,3-Neu5Ac and X-Gal-α-2,6-Neu5Ac, which were then used in the biochemical characterization of a linkage specific α-2,6-sialidase [23]. By replacing H 2 O with D 2 O, the mechanistic action of the first two enzymes in this reaction cascade, GlcNAc 2-epimerase, and sialic acid aldolase, allowed the exchange of up to three protons with deuterium atoms: in a recent work, we showed that the epimerization reaction of GlcNAc 2-epimerases is based on a deprotonation/reprotonation mechanism, which allowed the exchange of a single proton at the C2 position of GlcNAc or ManNAc during the epimerization reaction [24].…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of 9a was based on a procedure described previously [23,32], with slight modifications and performing the enzymatic reaction in D 2 O instead of H 2 O; in brief, the one-pot four-enzyme reaction was carried out using a lyophilized mixture of MES buffer (50 mM, pH 6.5) contained GlcNAc (10 mmol), CTP (0.15 mmol), pyruvate (0.25 mmol), MgCl 2 (0.05 mmol), PhGn2E (5 mU), EcNeuAld (5 mU), NmCTT (5 mU) and CjSiaT3 (5 mU). The mixture was dissolved in D 2 O (50 mL), and then X-Gal (0.1 mmol, dissolved in 0.5 mL of DMF) was added.…”
Section: Methodsmentioning
confidence: 99%
“…The Flitsch group has also identified a promising α-2,6-selective pseudosialidase that functions by promoting the reverse reaction (hydrolysis) of a sialyltransferase from Photobacterium sp. JT-ISH-224 by adding cytidine monophosphate to the assay . None of the reported sialidases have a preference for removing sialic acid from N- vs O-linked glycans.…”
Section: Enzymatic Engineeringmentioning
confidence: 99%